Effect of Cylinder Rotation Speed on Corn Drying Characteristics in a Rotary Dryer - Habibi, Muhammad Al Fatih; Sutanto, Rudy; Wirawan, Made (Institut Teknologi Adhi Tama Surabaya, Indonesia, 2026)
Corn has a high post-harvest moisture content (20-40%), making drying very important to maintain quality and extend shelf life. This study investigated the effect of drum rotation speed in a rotary dryer on the drying characteristics of corn and compared it with solar drying. The drying method was carried out using an LPG-fueled rotary dryer with an inlet air temperature of 70°C and an air flow velocity of 7.9 m/s. The drum rotation speed was varied at 6 rpm, 9 rpm, and 12 rpm with an initial corn mass of 5 kg. Drying was carried out for 6 hours. And data collection was carried out every 30 minutes during the drying process. As a result, a higher drum rotation speed significantly increased the drying rate. A speed of 12 rpm showed the best performance with a maximum drying rate of 0.46 kg/hour and an average of 0.24 kg/hour. However, the highest energy efficiency was obtained at a speed of 6 rpm, indicating that lower speeds require less energy despite longer drying times. Overall, the rotary dryer performed better than solar drying in reducing corn moisture content more quickly, stably, and controlled in a shorter time